PERCEPTION OF NATURAL SCIENCES’ TEACHER AND PROSPECTIVE TEACHER ON UNDERSTANDING LOW CARBON STEM LEARNING PLAN - Annisa Nur Khasanah; Riezky Maya Probosari; Sri Widoretno; Nurma Yunita Indriyani (ATRIUM PENDIDIKAN BIOLOGI, 2021)
The perception of science teachers and pre-service science teachers about the 'Low Carbon STEM' lesson plans, which is a new learning approach, makes the perspective of science teachers and pre service science teachers different. This difference results in differences in the implementation of the Low Carbon STEM lesson plan in the future. The objectives of this study include 1) to determine the perception of science teachers and pre service science teachers to Low Carbon STEM Lesson Plans, 2) to recommend one form of science learning approach that is Low Carbon-based STEM. The method used in this research is the mixed method, which combines quantitative and qualitative methods with data collection techniques using questionnaires. Questionnaires were distributed to science teachers and prospective science teachers using a rating scale of 1-4. The results of the questionnaire were calculated quantitatively and then described qualitatively. Respondents were members of the Focus Group Discussion (FGD) consisting total of 37 respondents. This study concludes that the tenth aspect received the most agreed responses with a percentage of 86.5% while the sixth aspect received the most disagree responses with a percentage of 89,2%.